A 2D hydrodynamic model for shallow water flows with significant infiltration losses. Issue 10 (26th February 2020) - Ni, Yufang; Cao, Zhixian; Liu, Qing; Liu, Qingquan
Abstract: Infiltration losses may be significant and warrant proper incorporation into mathematical models for river floods in arid and semi‐arid areas, rainfall‐induced surface runoffs in watersheds and swashes on beaches. Here, a depth‐averaged two‐dimensional hydrodynamic model is presented for such processes based on the cell‐centred finite volume method on unstructured meshes, with the full Green‐Ampt equation evaluating the infiltration rate. A local time stepping strategy is employed along with thread parallelization with Open Multi‐processing and high‐performance computing to reduce model run time and therefore facilitate applications for large‐scale processes. The numerical solutions generally agree with the experimental and field‐measured data for typical cases with significant infiltration losses. The case study shows that neglecting infiltration leads to an overestimated discharge hydrograph, which cannot be compensated by means of varied bed resistance as estimated by Manning roughness, and the infiltration parameters play disparate roles in modifying shallow flows compared with Manning roughness. In addition, infiltration affects bed shear stress, which in turn modifies the critical bed sediment size that could be initiated for incipient motion by the flow and therefore needs to be properly accounted for when sediment transport and morphological evolution are to be resolved. Abstract : An efficient model is proposed for shallow water flows featuring infiltration losses, with experimental and real cases reproduced satisfactorily. The neglect of infiltration leads to an overestimated discharge hydrograph and the infiltration parameters play disparate roles compared with Manning roughness. Infiltration loss may largely alter the threshold condition for sediment movement and thus warrants incorporation in the model.